Upaya Pembentukan Guru Ideal Melalui Penerapan Standar Kompetensi Guru Profesional di SMP Negeri 47 Bulukumba - Vera, Andi Ana; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine how the implementation of teacher competency standards contributes to shaping the ideal teacher at SMP Negeri 47 Bulukumba. The research is grounded in the concern over the declining quality of national education, which is closely related to teacher competence and professionalism. Employing a qualitative method with a descriptive narrative approach, data were collected through observation, interviews, and triangulation. The findings indicate that an ideal teacher is defined not only by teaching ability but also by personal integrity, pedagogical, social, and professional competencies, as well as by receiving proper recognition and legal protection. A comprehensive effort is required—from both individual educators and government policies—to achieve quality and sustainable education. In conclusion, ideal teachers must be well-educated, well-trained, well-paid, well-protected, and well-managed in order to perform their professional duties effectively.